Nanostructured Materials and Nanotechnology V : Ceramic Engineering and Science Proceedings. - Mathur, Sanjay (John Wiley & Sons, 2011)
A collection of papers from The American Ceramic Society's 35th International Conference on Advanced Ceramics and Composites, held in Daytona Beach, Florida, January 23-28, 2011. This issue includes papers presented in the 5th International Symposium on Nanostructured Materials and Nanotechnology on topics such as Nanotubes, Nanorods, Nanowires and other One-dimensional Structures; Nanostructured Membranes, Thin Films, and Functional Coatings; Synthesis, Functionalization and Processing of Nanostructured Materials; and Advanced Applications.